The association between oral and gut microbiota in male patients with alcohol dependence - Hu, Lingming; Ni, Zhaojun; Zhao, Kangqing; Li, Xiangxue; Gao, Xuejiao; Kang, Yulin; Yu, Zhoulong; Qin, Ying; Zhao, Jingwen; Peng, Wenjuan; Lu, Lin; Sun, Hongqiang (Frontiers in Microbiology, 2023)
The relationship between oral and gut microbiota in alcohol dependence (AD) is not well understood, particularly the effects of oral microbiota on the intestinal microbiota. The current study aimed to explore the association between oral and gut microbiota in AD to clarify whether oral microbiota could ectopically colonize into the gut.Methods: 16S rRNA sequence libraries were used to compare oral and gut microbial profiles in persons with AD and healthy controls (HC). Source Tracker and NetShift were used to identify bacteria responsible for ectopic colonization and indicate the driver function of ectopic colonization bacteria.The α-diversity of oral microbiota and intestinal microbiota was significantly decreased in persons with AD (all p < 0.05). Principal coordinate analysis indicated greater similarity between oral and gut microbiota in persons with AD than that in HC, and oral-gut overlaps in microbiota were found for 9 genera in persons with AD relative to only 3 genera in HC. The contribution ratio of oral microbiota to intestinal microbiota composition in AD is 5.26% based on Source Tracker，and the AD with ectopic colonization showed the daily maximum standard drinks, red blood cell counts, hemoglobin content, and PACS scores decreasing (all p< 0.05).Results highlight the connection between oral-gut microbiota in AD and suggest novel potential mechanistic possibilities.